Biological activities of silver nanoparticles from Nothapodytes nimmoniana (Graham) Mabb. fruit extracts - G. Mahendran; B.D. Ranjitha Kumari (Food Science and Human Wellness)
In the present investigation, we have described the green biosynthesis of silver nanoparticles (AgNPs) using ripened fruit aqueous extract of Nothapodytes nimmoniana (Graham) Mabb. as capping agent. The antioxidant, anticancer and antimicrobial activities of AgNPs were also studied. UV analysis revealed that AgNPs had a sharp peak at 416 nm. X-ray diffraction (XRD) result confirmed the characteristic peaks indicated at 1 1 1, 2 0 0, 2 2 0 and 3 1 1 for the crystalline of the face centered cubic silver. The Scanning Electron Microscopy analysis results confirmed the spherical shaped of AgNPs with difference sizes of the particles and an average from 44 to 64 nm. Further, fruit extract and AgNPs were evaluated total phenolic, tannin and flavonoid contents and were subjected to assess their antioxidant potential using various in vitro systems such as using 1,1-diphenyl-2-picryl-hydrazyl (DPPH), 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), metal chelating, phosphomolybdenum and ferric reducing antioxidant power (FRAP) activities and antimicrobial activity against Bacillus subtilis, Pseudomonas aeruginosa, Klebsiella pneumoniae, Staphylococcus aureus and Escherichia coli. When compared to AgNPs, fruit extract exhibited uppermost radical scavenging activities. In addition, the cytotoxicity activity was determined by MTT assay. Our results clearly proved that biosynthesized AgNPs inhibited proliferation of HeLA cell line with an IC50 of 87.32 ± 1.43 μg/mL and antibacterial activity.